Lead-free solder paste and manufacturing process thereof

Through the combination of specific raw material ratios and nanopalladium and hydroxyl-terminated polydimethylsiloxane, the problem of insufficient stability and wetting properties of lead-free solder paste in long-term use is solved, significantly reducing the pore rate, improving welding quality and product reliability.

CN119549926AInactive Publication Date: 2025-03-04SHENZHEN HUAKE IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510016907.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lead-free solder paste may have microcracks and poor wetting properties during long-term use, resulting in poor welding and high pore rate, affecting welding quality and product reliability.

Method used

Specific raw material ratios are adopted, including tin-based alloy powder, flux, nanopalladium and hydroxy-terminated polydimethylsiloxane. The microstructure of solder joints is improved through nanopalladium, reducing hollow formation, and hydroxy-terminated polydimethylsiloxane improves wetting performance.

Benefits of technology

It improves the long-term stability, wetting performance and reduces pore rate of lead-free solder paste, and enhances the reliability and welding quality of solder points.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of welding materials. The invention discloses lead-free solder paste and a manufacturing process thereof. The lead-free solder paste is prepared from the following raw materials: tin-based alloy powder, scaling powder, nano palladium and hydroxyl-terminated polydimethylsiloxane. The soldering flux comprises the following raw materials: rosin, an active agent, a thixotropic agent, an antioxidant, a film-forming agent and a solvent. The preparation process comprises the following steps: S1, mixing rosin, an active agent and a solvent, heating, stirring and cooling to prepare a premixed solution; s2, a thixotropic agent, an antioxidant and a film-forming agent are sequentially added into the premixed liquid, stirring and mixing are conducted, and scaling powder is prepared; and S3, the scaling powder, the tin-based alloy powder, the nano palladium and the hydroxyl-terminated polydimethylsiloxane are stirred and mixed, and the lead-free solder paste is prepared. The prepared lead-free solder paste is good in long-term stability, good in wettability and low in void ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of welding materials, and in particular to a lead-free solder paste and a manufacturing process thereof. Background Art

[0002] With the rapid development of the electronics manufacturing industry and increasingly stringent environmental regulations, lead-free has become an important trend in the electronics assembly industry. Traditional tin-lead solder is widely used in the manufacture of electronic products due to its low melting point and good welding performance. However, the lead element in tin-lead solder not only pollutes the environment, but also poses potential harm to human health. Therefore, countries around the world have successively introduced a series of restrictions on the use of hazardous substances in electronic products, such as the EU's RoHS directive, and traditional lead-containing solder has gradually been replaced by lead-free solder.

[0003] Lead-free solder paste is an important lead-free solder, which is mainly used in the soldering process of surface mount technology (SMT) to fix electronic components. The main components of lead-free solder paste include metals such as tin, silver, and copper, among which the common formulation is the SnAgCu (SAC) series. Compared with traditional tin-lead solder, lead-free solder paste does not contain lead, which reduces environmental pollution and potential harm to human health; and lead-free alloys have better strength and heat resistance, improve the reliability of solder joints, and can adapt to a wider range of soldering temperature, suitable for substrates and components of various materials.

[0004] However, in actual application, lead-free solder paste still has some limitations. For example, lead-free alloys may develop microcracks during long-term use, reducing the reliability of solder joints and affecting the service life of the product. In addition, the wettability of lead-free solder is poor, especially in high-speed soldering or complex designs, which may lead to poor soldering, affecting the soldering quality and the overall performance of the product. In addition, lead-free solder has a higher melting point and requires a higher soldering temperature, which may lead to more void formation. If the gas generated during the welding process fails to escape in time, it will also form voids inside the solder joint, thus affecting the reliability and mechanical strength of the electrical connection.

[0005] Therefore, it is urgent to develop a lead-free solder paste with good long-term stability, good wetting performance and low porosity. Summary of the invention

[0006] In order to solve at least one of the above technical problems and develop a lead-free solder paste with good long-term stability, good wetting performance and low porosity, the present application provides a lead-free solder paste and a production process thereof.

[0007] On the one hand, the present application provides a lead-free solder paste, comprising tin-based alloy powder, flux, nano palladium and hydroxyl-terminated polydimethylsiloxane, wherein the weight ratio of the tin-based alloy powder, flux, nano palladium and hydroxyl-terminated polydimethylsiloxane is 85-95:5-15:0.01-0.1:0.1-0.3; The soldering flux comprises, by mass percentage, 40% to 60% of rosin, 1% to 5% of activator, 1% to 3% of thixotropic agent, 0.1% to 1% of antioxidant, 1% to 5% of film former, and the balance is solvent.

[0008] By adopting the above technical scheme, the present application adopts specific raw materials and proportions to obtain a lead-free solder paste with good long-term stability, good wetting performance and low porosity. The present application adds nano-palladium, which can improve the stability of the microstructure of the solder joint and reduce the formation of microcracks. The high surface activity of nano-palladium can also improve the microstructure of the solder joint, reduce the formation of voids during the welding process, and reduce the porosity. The present application adds hydroxyl-terminated polydimethylsiloxane, which can improve the wetting performance of the solder paste and reduce poor welding.

[0009] Optionally, the tin-based alloy powder is selected from one of tin-silver-copper tin powder, tin-antimony tin powder and tin-silver-indium tin powder.

[0010] By adopting the above technical scheme, the tin-based alloy powder of the present application has good wettability and welding performance, and is suitable for welding in various application scenarios. Reasonable selection of tin-based alloy powder can further improve the long-term stability, wettability and reduce the porosity of lead-free solder paste, thereby meeting the needs of high-performance electronic assembly.

[0011] Optionally, the weight ratio of the nano palladium to the hydroxyl-terminated polydimethylsiloxane is 0.1-0.4:1.

[0012] By adopting the above technical solution, the present application adds nano palladium and hydroxyl-terminated polydimethylsiloxane, which work together to further improve the wetting performance, reduce the formation of holes, and improve the reliability of the welding points.

[0013] Optionally, the average particle size of the nano-palladium is 5 to 20 nm.

[0014] By adopting the above technical solution, the average particle size of the nano-palladium of the present application is 5 to 20 nm, which has higher surface activity, good dispersibility, and can also reduce the formation of voids during the welding process.

[0015] Optionally, the active agent is selected from at least one of zinc chloride, citric acid and succinic acid.

[0016] By adopting the above technical solution, the active agent of the present application can remove oxides on the metal surface, improve wettability, and thus improve welding quality.

[0017] Optionally, the thixotropic agent is selected from at least one of hydroxyethyl cellulose, polyacrylamide and hydrogenated castor oil.

[0018] By adopting the above technical solution, the thixotropic agent of the present application can improve thixotropy, help control the deposition amount of solder paste, reduce the formation of voids during the welding process, and improve the welding quality.

[0019] Optionally, the antioxidant is selected from at least one of 2,6-di-tert-butyl-4-methylphenol, dilauryl thiodipropionate and N,N'-diphenyl-1,4-phenylenediamine.

[0020] By adopting the above technical solution, the antioxidant of the present application can improve the antioxidant performance of the flux, prevent the metal surface from oxidizing during the welding process, improve the welding quality, and also help to extend the service life of the flux.

[0021] Optionally, the film-forming agent is selected from at least one of polyvinyl butyral, polyvinyl pyrrolidone and methyl hydrogenated rosin.

[0022] By adopting the above technical solution, the film-forming agent of the present application can form a protective film on the surface of the solder joint, thereby improving the mechanical strength of the solder joint and reducing oxidation of the solder joint during long-term use.

[0023] Optionally, the solvent is selected from at least one of ethanol, isopropanol and methyl ethyl ketone.

[0024] By adopting the above technical solution, the solvent of the present application can improve the fluidity and wettability of the flux.

[0025] In a second aspect, the present application provides a process for producing the above-mentioned lead-free solder paste, comprising the following steps: S1, mixing the rosin, the activator and the solvent, heating to 130-150° C., stirring for 30-60 min, and cooling to 30-50° C. to obtain a premixed solution; S2, adding the thixotropic agent, antioxidant and film-forming agent to the premixed liquid in sequence, stirring and mixing, to obtain a soldering flux; S3, stirring and mixing the soldering flux, tin-based alloy powder, nano-palladium and hydroxyl-terminated polydimethylsiloxane to prepare a lead-free solder paste.

[0026] By adopting the above technical scheme, the preparation method of the present application is simple to operate and has high preparation efficiency. The present application gradually mixes the raw materials to ensure the uniform dispersion of the components in the flux and improves the overall performance of the lead-free solder paste. The addition of nano-palladium and hydroxyl-terminated polydimethylsiloxane reduces the formation of holes during the welding process. The preparation process is energy-saving and emission-reducing, and pollution-free.

[0027] In summary, the present invention includes at least one of the following beneficial technical effects: 1. This application adopts specific raw materials and proportions to produce lead-free solder paste with good long-term stability, good wetting performance and low porosity.

[0028] 2. The application adds nano-palladium, which can improve the microstructure of the solder joint, reduce the formation of voids during the welding process, and reduce the porosity.

[0029] 3. The addition of hydroxyl-terminated polydimethylsiloxane in this application can improve the wetting properties of solder paste and reduce soldering defects.

[0030] 4. The preparation method of the present application is simple to operate and has high preparation efficiency. The present application gradually mixes the raw materials to ensure the uniform dispersion of the components in the flux and improves the overall performance of the lead-free solder paste. DETAILED DESCRIPTION

[0031] The present application is further described in detail below with reference to the embodiments.

[0032] The present application designs a lead-free solder paste, comprising tin-based alloy powder, soldering flux, nano palladium and hydroxyl-terminated polydimethylsiloxane, wherein the weight ratio of the tin-based alloy powder, soldering flux, nano palladium and hydroxyl-terminated polydimethylsiloxane is 85-95: 5-15: 0.01-0.1: 0.1-0.3; The soldering flux comprises, by mass percentage, 40% to 60% of rosin, 1% to 5% of activator, 1% to 3% of thixotropic agent, 0.1% to 1% of antioxidant, 1% to 5% of film former, and the balance is solvent.

[0033] The lead-free solder paste of the present application is prepared by the following method, comprising the following steps: S1, mixing the rosin, the activator and the solvent, heating to 130-150° C., stirring for 30-60 min, and cooling to 30-50° C. to obtain a premixed solution; S2, adding the thixotropic agent, antioxidant and film-forming agent to the premixed liquid in sequence, stirring and mixing, to obtain a soldering flux; S3, stirring and mixing the soldering flux, tin-based alloy powder, nano-palladium and hydroxyl-terminated polydimethylsiloxane to prepare a lead-free solder paste.

[0034] The present application designs a technical solution to address the problems of existing lead-free solder pastes, such as insufficient long-term stability, insufficient wetting performance, and high void rate.

[0035] The raw materials used in this application are as follows: Hydroxy-terminated polydimethylsiloxane: Wuhan Kanosi Technology Co., Ltd., purity: 99%.

[0036] Rosin: CAS: 8050-09-7.

[0037] Zinc chloride: CAS: 7646-85-7.

[0038] Citric acid: CAS: 77-92-9.

[0039] Hydroxyethyl cellulose: CAS: 9004-62-0.

[0040] Hydrogenated castor oil: CAS: 61788-85-0.

[0041] Dilauryl thiodipropionate: CAS: 123-28-4.

[0042] N,N'-Diphenyl-1,4-phenylenediamine: CAS: 74-31-7.

[0043] Polyvinylpyrrolidone: CAS: 9003-39-8.

[0044] Methyl hydrogenated rosinate: CAS: 8050-15-5.

[0045] Isopropyl alcohol: CAS: 67-63-0.

[0046] Methyl ethyl ketone: CAS: 78-93-3. Specific embodiments

[0047] Examples 1 to 3 Example 1 This embodiment provides a lead-free solder paste, comprising tin-based alloy powder, soldering flux, nano palladium and hydroxyl-terminated polydimethylsiloxane, wherein the weight ratio of the tin-based alloy powder, soldering flux, nano palladium and hydroxyl-terminated polydimethylsiloxane is 85:15:0.01:0.1; The flux comprises, by mass percentage, 40% of rosin, 5% of activator, 1% of thixotropic agent, 0.1% of antioxidant, 5% of film-forming agent, and the balance of solvent.

[0048] The tin-based alloy powder is SAC 305 alloy powder; the average particle size of nano-palladium is 12 nm; the active agent is citric acid; the thixotropic agent is hydroxyethyl cellulose; the antioxidant is dilauryl thiodipropionate; the film-forming agent is polyvinyl pyrrolidone; and the solvent is isopropyl alcohol.

[0049] The production process includes the following steps: S1. Mix rosin, activator and solvent, heat to 130°C, stir for 60 minutes, and cool to 30°C to prepare a premixed solution; S2, adding a thixotropic agent, an antioxidant, and a film-forming agent to the premixed liquid in sequence, stirring and mixing, to obtain a soldering flux; S3, mixing the soldering flux, tin-based alloy powder, nano-palladium and hydroxyl-terminated polydimethylsiloxane to prepare a lead-free solder paste.

[0050] Example 2 This embodiment provides a lead-free solder paste, comprising tin-based alloy powder, soldering flux, nano palladium and hydroxyl-terminated polydimethylsiloxane, wherein the weight ratio of the tin-based alloy powder, soldering flux, nano palladium and hydroxyl-terminated polydimethylsiloxane is 90:10:0.05:0.2; The flux comprises, by weight percentage, 50% of rosin, 3% of activator, 2% of thixotropic agent, 0.5% of antioxidant, 3% of film-forming agent, and the balance of solvent.

[0051] The tin-based alloy powder is SAC 305 alloy powder; the average particle size of nano-palladium is 12 nm; the active agent is citric acid; the thixotropic agent is hydroxyethyl cellulose; the antioxidant is dilauryl thiodipropionate; the film-forming agent is polyvinyl pyrrolidone; and the solvent is isopropyl alcohol.

[0052] The production process includes the following steps: S1. Mix rosin, activator and solvent, heat to 140°C, stir for 45 minutes, cool to 40°C to obtain a premixed liquid; S2. Add thixotropic agent, antioxidant and film-forming agent to the premixed liquid in sequence, stir and mix to obtain flux; S3, mixing the soldering flux, tin-based alloy powder, nano-palladium and hydroxyl-terminated polydimethylsiloxane to prepare a lead-free solder paste.

[0053] Example 3 This embodiment provides a lead-free solder paste, comprising tin-based alloy powder, soldering flux, nano palladium and hydroxyl-terminated polydimethylsiloxane, wherein the weight ratio of the tin-based alloy powder, soldering flux, nano palladium and hydroxyl-terminated polydimethylsiloxane is 95:5:0.1:0.3; The soldering flux comprises, by weight percentage, 60% of rosin, 1% of activator, 3% of thixotropic agent, 1% of antioxidant, 1% of film-forming agent, and the balance of solvent.

[0054] The tin-based alloy powder is SAC 305 alloy powder; the average particle size of nano-palladium is 12 nm; the active agent is citric acid; the thixotropic agent is hydroxyethyl cellulose; the antioxidant is dilauryl thiodipropionate; the film-forming agent is polyvinyl pyrrolidone; and the solvent is isopropyl alcohol.

[0055] The production process includes the following steps: S1. Mix rosin, activator and solvent, heat to 150°C, stir for 30 minutes, and cool to 50°C to obtain a premixed liquid; S2. Add thixotropic agent, antioxidant and film-forming agent to the premixed liquid in sequence, stir and mix, and obtain solder flux; S3, mixing the soldering flux, tin-based alloy powder, nano-palladium and hydroxyl-terminated polydimethylsiloxane to prepare a lead-free solder paste.

[0056] Comparative Examples 1 to 4 Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that, in Comparative Example 1, nano palladium and hydroxyl-terminated polydimethylsiloxane are not added.

[0057] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that no nano palladium is added in Comparative Example 2.

[0058] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that no hydroxyl-terminated polydimethylsiloxane is added in Comparative Example 3.

[0059] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that the rosin, the activator and the solvent are not premixed in Comparative Example 4. The specific preparation method is as follows: S1. Stirring and mixing rosin, activator, thixotropic agent, antioxidant, film-forming agent and solvent to prepare soldering flux; S2, mixing flux, tin-based alloy powder, nano-palladium and hydroxyl-terminated polydimethylsiloxane to prepare lead-free solder paste.

[0060] Experimental testing Test items and test methods Long-term stability: The prepared lead-free solder paste was sealed and stored at 25°C for 6 months to observe whether stratification and precipitation occurred; Expansion rate: The expansion rate of the lead-free solder paste was tested according to JIS Z3284; Wetting performance: The wetting performance of lead-free solder paste is evaluated according to the solder paste wettability evaluation standard in SJ / T 11186-2019 "General Specification for Solder Paste"; Porosity: Test the porosity of solder joints according to IPC-TM-650.

[0061] The lead-free solder pastes prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested for long-term stability, expansion rate, wetting performance and void ratio. The test results are shown in Table 1.

[0062] Table 1 Long-term stability Expansion rate / % Wetting properties Porosity / % Example 1 No stratification, no precipitation 83.4 Level 1 6.2 Example 2 No stratification, no precipitation 84.6 Level 1 5.7 Example 3 No stratification, no precipitation 83.8 Level 1 6.0 Comparative Example 1 No stratification, no precipitation 71.5 Level 2 10.5 Comparative Example 2 No stratification, no precipitation 79.4 Level 1 10.1 Comparative Example 3 No stratification, no precipitation 73.0 Level 2 6.8 Comparative Example 4 There is stratification and precipitation 78.5 Level 1 8.2 From the test results in Table 1, it can be seen that the lead-free solder pastes prepared in Examples 1 to 3 have good long-term stability, good wetting properties, and low void ratio.

[0063] Comparative Example 1 did not add nano palladium and hydroxyl-terminated polydimethylsiloxane, Comparative Example 2 did not add nano palladium, and Comparative Example 3 did not add hydroxyl-terminated polydimethylsiloxane. The wetting properties of the lead-free solder pastes prepared in Comparative Examples 1 to 3 were reduced, and the porosity was significantly increased.

[0064] In Comparative Example 4, the raw materials of the flux were mixed and stirred together without being added sequentially, and the long-term stability of the obtained lead-free solder paste deteriorated, the expansion rate decreased, and the void rate increased.

[0065] Embodiments 4 to 12 Example 4 The difference between Example 4 and Example 2 is that in Example 4, the weight ratio of nano palladium to hydroxyl-terminated polydimethylsiloxane is 0.1:1, and the total proportion of nano palladium and hydroxyl-terminated polydimethylsiloxane is 0.25.

[0066] Example 5 The difference between Example 5 and Example 2 is that in Example 5, the weight ratio of nano palladium to hydroxyl-terminated polydimethylsiloxane is 0.4:1, and the total proportion of nano palladium and hydroxyl-terminated polydimethylsiloxane is 0.25.

[0067] Example 6 The difference between Example 6 and Example 2 is that in Example 6, the average particle size of nano-palladium is 5 nm.

[0068] Example 7 The difference between Example 7 and Example 2 is that in Example 7, the average particle size of nano-palladium is 20 nm.

[0069] Example 8 The difference between Example 8 and Example 2 is that in Example 8, the active agent is zinc chloride.

[0070] Example 9 The difference between Example 9 and Example 2 is that in Example 9, the thixotropic agent is hydrogenated castor oil.

[0071] Example 10 The difference between Example 10 and Example 2 is that in Example 10, the antioxidant is N,N'-diphenyl-1,4-phenylenediamine.

[0072] Embodiment 11 The difference between Example 11 and Example 2 is that in Example 11, the film-forming agent is methyl hydrogenated rosin.

[0073] Example 12 The difference between Example 12 and Example 2 is that in Example 12, the solvent is methyl ethyl ketone.

[0074] The lead-free solder pastes prepared in Examples 4 to 12 were tested for long-term stability, expansion rate, wetting performance and void ratio. The test results are shown in Table 2.

[0075] Table 2 Long-term stability Expansion rate / % Wetting properties Porosity / % Example 4 No stratification, no precipitation 84.2 Level 1 6.4 Example 5 No stratification, no precipitation 83.9 Level 1 6.0 Example 6 No stratification, no precipitation 84.5 Level 1 5.8 Example 7 No stratification, no precipitation 84.0 Level 1 6.1 Example 8 No stratification, no precipitation 84.5 Level 1 5.9 Example 9 No stratification, no precipitation 84.7 Level 1 5.5 Example 10 No stratification, no precipitation 84.6 Level 1 5.7 Embodiment 11 No stratification, no precipitation 84.7 Level 1 5.6 Example 12 No stratification, no precipitation 84.5 Level 1 5.8 From the test results in Table 2, it can be seen that the difference between Example 4 and Example 5 and Example 2 is that the weight ratios of nano-palladium and hydroxyl-terminated polydimethylsiloxane are different, among which the lead-free solder paste prepared in Example 2 has the best expansion rate and wetting performance and the lowest void rate.

[0076] The difference between Example 6 and Example 7 and Example 2 is that the average particle sizes of nano-palladium are different. Among them, the lead-free solder paste prepared in Example 2 has the best expansion rate and the lowest hole rate.

[0077] The expansion rate, wetting performance and hole rate of the lead-free solder paste prepared in Examples 8 to 12 are similar to those in Example 2.

[0078] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A lead-free solder paste, characterized in that: It comprises tin-based alloy powder, soldering flux, nano palladium and hydroxyl-terminated polydimethylsiloxane, wherein the weight ratio of the tin-based alloy powder, soldering flux, nano palladium and hydroxyl-terminated polydimethylsiloxane is 85-95:5-15:0.01-0.1:0.1-0.3; The soldering flux comprises, by mass percentage, 40% to 60% rosin, 1% to 5% activator, 1% to 3% thixotropic agent, 0.1% to 1% antioxidant, 1% to 5% film-forming agent, and the balance is solvent.

2. The lead-free solder paste according to claim 1, characterized in that: The tin-based alloy powder is selected from tin-silver-copper tin powder, tin-antimony tin powder, and tin-silver-indium tin powder.

3. The lead-free solder paste according to claim 1, characterized in that: The weight ratio of the nano palladium to the hydroxyl-terminated polydimethylsiloxane is 0.1-0.4:

1.

4. The lead-free solder paste according to claim 1, characterized in that: The average particle size of the nano palladium is 5-20 nm.

5. The lead-free solder paste according to claim 1, characterized in that: The active agent is selected from at least one of zinc chloride, citric acid and succinic acid.

6. The lead-free solder paste according to claim 1, characterized in that: The thixotropic agent is selected from at least one of hydroxyethyl cellulose, polyacrylamide and hydrogenated castor oil.

7. The lead-free solder paste according to claim 1, characterized in that: The antioxidant is selected from at least one of 2,6-di-tert-butyl-4-methylphenol, dilauryl thiodipropionate and N,N'-diphenyl-1,4-phenylenediamine.

8. The lead-free solder paste according to claim 1, characterized in that: The film-forming agent is selected from at least one of polyvinyl butyral, polyvinyl pyrrolidone and methyl hydrogenated rosin.

9. The lead-free solder paste according to claim 1, characterized in that: The solvent is selected from at least one of ethanol, isopropanol and methyl ethyl ketone.

10. A process for producing a lead-free solder paste according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Mix the rosin, the activator and the solvent, heat to 130-150° C., stir for 30-60 min, and cool to 30-50° C. to obtain a premixed solution; S2, adding the thixotropic agent, antioxidant and film-forming agent to the premixed liquid in sequence, stirring and mixing, to obtain a soldering flux; S3, stirring and mixing the soldering flux, tin-based alloy powder, nano-palladium and hydroxyl-terminated polydimethylsiloxane to prepare a lead-free solder paste.